Distribution of Mycobacterium avium complex isolates in tissue samples of pigs fed peat naturally contaminated with mycobacteria as a supplement - Matlova, Ludmila; Dvorska, Lenka; Ayele, Wuhib Yayo; Bartos, Milan; Amemori, Takashi; Pavlik, Ivo (Journal of clinical microbiology, 2005)
In early 1999, there was an increased incidence of tuberculous lesions in the lymph nodes of slaughtered pigs in the Czech Republic. In part 1 of this study, tuberculous lesions were detected in 140 (62%) tissue samples collected from pigs coming from 15 farms in 15 districts at routine veterinary meat inspections in abattoirs. Mycobacteria were isolated from 37 (16%) tissue samples: 34 Mycobacterium avium subsp. hominissuis isolates and three environmentally derived mycobacteria. In search of infection sources, M. avium subsp. hominissuis was isolated from 38 (79%) samples of peat used as a feed supplement. In part 2 of our study, the head, mesenteric, and inguinal lymph nodes of 117 randomly selected slaughtered pigs from one farm with young piglets fed peat as a supplement were investigated for mycobacterial infection. From 65 (56%) pigs, a total of 76 mycobacterial isolates were identified (56 M. avium subsp. hominissuis isolates, 5 M. avium subsp. avium isolates, 3 M. intracellulare isolates, and 12 environmentally derived mycobacterial isolates). IS1245 restriction fragment length polymorphism (RFLP) types with >20 bands of 45 distinct RFLP types were found in 49 M. avium subsp. hominissuis isolates from pigs (n = 31) and peat (n = 18). Identical RFLP types were found in only four pig isolates. Five randomly selected isolates from pigs and peat were subcultured to six independent clones or colonies. Among the IS1245 RFLP types of 30 clones, identical RFLP types obtained from pigs and peat were identified, which confirmed the hypothesis that peat contaminated with mycobacteria represents a significant source of mycobacterial infection for pigs.
Keywords: DNA Transposable Elements; Swine; půdní mikrobiologie; Mycobacterium avium komplex; Mycobacterium avium Complex; Animal Feed; Animals; polymorfismus délky restrikčních fragmentů; krmivo pro zvířata; Polymorphism, Restriction Fragment Length; zvířata; prasata; transpozibilní elementy DNA; Soil Microbiology